Anxiety in children and youth: Part 1—Diagnosis. Issue 1 (28th February 2023) - Klein, Benjamin; Rajendram, Rageen; Hrycko, Sophia; Poynter, Aven; Ortiz-Alvarez, Oliva; Saunders, Natasha; Andrews, Debra
Abstract: Anxiety disorders are the most common mental health concerns affecting Canadian children and adolescents. The Canadian Paediatric Society has developed two position statements that summarize current evidence regarding the diagnosis and management of anxiety disorders. Both statements offer evidence-informed guidance to support paediatric health care providers (HCPs) making decisions around the care of children and adolescents with these conditions. The objectives of Part 1, which focuses on assessment and diagnosis, are to: (1) review the epidemiology and clinical characteristics of anxiety disorders and (2) describe a process for assessment of anxiety disorders. Specific topics are reviewed, including prevalence, differential diagnosis, co-occurring conditions, and the process of assessment. Approaches are offered for standardized screening, history-taking, and observation. Associated features and indicators that distinguish anxiety disorders from developmentally appropriate fears, worries, and anxious feelings are considered. Note that when the word 'parent' (singular or plural) is used, it includes any primary caregiver and every configuration of family.